Evaluation of a group-based hypertension self-management education programme among hypertensive community dwellers - Yatim, Hanisah Mohd; Wong, Yuet Yen; Lim, Seng Hock; Hassali, Mohamad Azmi; Hong, Yet Hoi; Dali, Ahmad Fauzi; Neoh, Chin Fen (Elsevier, 2018)
Introduction: Low self-efficacy level among patients with hypertension could be the underlying reason for poor daily disease self-management, leading to suboptimal blood pressure (BP) control. A structured, group-based hypertension self-management education (HSME) programme could be a potential solution to improve BP control; however, impact of HSME programme in the Malaysian setting remain unknown. This study aimed to evaluate the impact of a structured, group-based HSME programme on hypertensive patients’ clinical and psychosocial outcomes. Methods: A pretest-posttest quasi-experimental study design was employed. Participants attended a total of 4-weekly of the HSME programme at a community hall. Participants’ clinical and psychosocial outcomes were assessed at three time-points. Data were analysed using IBM SPSS version 23.0. Results: Forty-five participants consented to join the programme, with 36 (80.0%) attended two or more sessions. At post 1-week of intervention, participants were found to have significant improvement in high-density lipoprotein (HDL) cholesterol (p = 0.001), number of days spent on vigorous physical activity (p = 0.007), motivation (p = 0.005) and self-efficacy (p = 0.005). At 2-month, participants have sustained increased in HDL cholesterol, motivation and self-efficacy, in addition to a significant improvement in self-care behaviour (p = 0.002). Conclusions: The short-term HSME programme elicited certain positive clinical and psychosocial outcomes, a larger scale randomised controlled trial should be carried out to determine the effective elements of the HSME programme that lead to the self-care behavioural changes and to evaluate the long-term impacts of sustained self-care practices among community dwellers with hypertension.